Re: Need help with solving problem
- To: mathgroup at smc.vnet.net
- Subject: [mg5372] Re: [mg5339] Need help with solving problem
- From: Francisco Edmundo de Andrade <edmundo at lia.ufc.br>
- Date: Thu, 5 Dec 1996 14:50:15 -0500
- Sender: owner-wri-mathgroup at wolfram.com
On Wed, 27 Nov 1996, Ingimar V=F6lundarson wrote: > Can anyone help me with this problem? >=20 > (4^x)+(2^x)-2=3D0 >=20 > Everyone can see that x=3D0 but: >=20 > (4^x)+(2^x)-2=3D0 =3D> > 2*(2^x)+(2^x)-2=3D0 =3D> > 2y+y-2=3D0 =3D> ;(let y=3D2^x) > 3y=3D2 =3D> > y=3D2/3 =3D> > 2^x=3D2/3 =3D> ;(let 2^x=3Dy) > lg(2^x)=3Dlg(2/3) =3D>=20 > x*lg(2)=3Dlg(2/3) =3D> > x=3Dlg(2/3)/lg(2) Which is not true!!! >=20 > Am I doing something wrong? >=20 > Please E-mail an answer to: > ingimar.volundarson at mailbox.swipnet.se >=20 > Thanx in advance! >=20 >=20 >=20 Yes, there is an error in the first equivalence: (4^x)+(2^x)-2=3D0 <> 2*(2^x)+(2^x)-2=3D0 because (4^x)+(2^x)-2=3D0 =3D (2^x)*(2^x)+(2^x)-2=3D0 So, the sequence must be continued: y^2+y-2=3D0 ; 2^x->y y=3D-2 or y=3D1 2^x=3D-2 or 2^x=3D1 The first equation is invalid, so the solution is x=3D0. (Edmundo's contribuition 1996) With Kindest regards Edmundo ----------------------------- edmundo at lia.ufc.br Universidade Federal do Ceara Fortaleza - Ceara - BRAZIL -----------------------------